The Impact of Digital Marketing on Local Businesses - Yendra, Yendra; Zakaria, Zakaria; Noy, Ismail (Advances in Community Services Research, 2024)
Purpose: This study investigates how digital marketing impacts local businesses, focusing on its role in enhancing customer engagement, sales performance, and brand building. It aims to address the challenges local businesses face in adopting digital marketing tools and strategies to achieve sustainable growth and competitive advantage in a digital-first environment. Research Design and Methodology: A qualitative literature review method was used, incorporating systematic thematic analysis and meta-synthesis of existing academic studies. Relevant sources were selected from databases like Google Scholar, JSTOR, ScienceDirect, and ProQuest. The analysis emphasizes key digital marketing elements such as social media marketing, email marketing, and search engine optimization (SEO), particularly their effects on local businesses. Findings and Discussion: Digital marketing significantly boosts customer engagement by enhancing interaction and satisfaction through social media and email platforms. It increases sales and revenue via targeted advertising and improved online visibility through SEO. Additionally, digital marketing strengthens brand identities by enabling consistent and engaging content delivery. Challenges include continuous adaptation to digital trends and managing complex tools, highlighting the necessity for strategic planning and ongoing learning. Implications: This study emphasizes the need for local businesses to integrate digital marketing and invest in continuous skill development strategically. It provides practical insights for leveraging digital marketing to foster growth and resilience, contributing to academic and practical fields.